1983
DOI: 10.1002/pssb.2221150211
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic recombination in dependence on doping concentration and excitation level application to lead chalcogenides

Abstract: On the base of anisotropic and parabolic band structure recombination rates are calculated for the mixed crystals Pb0.78Sno.22Te and PbSo.lSeo.9 in dependence on non-equilibrium carrier concentration 6n up to 1020 cm-9 in a wide range of temperatures and doping levels. Degeneracy causes different changes of lifetimes or recombination rates for material with different activation energies of the recombination process. Both, weakening or strengthening of the known n2pp-law of the Auger transition rate can occur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 12 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…A particular feature of this system-i.e., their near ''mirror'' conduction and valence bands-has been cited as potentially leading to much smaller Auger scattering rates than found in III-V material systems. However, theory predicts that there may nevertheless still remain a substantial contribution to this unwanted recombination process through intervalley scattering, [1][2][3][4] although later theories, [2][3][4] including more realistic band-structure pictures, suggest that this should not be as serious as originally predicted. 1 Understanding accurately how the recombination processes change with carrier density is important for emission devices which operate far from equilibrium, and in particular in the continuing quest for the development of compact MIR room-temperature lasers.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A particular feature of this system-i.e., their near ''mirror'' conduction and valence bands-has been cited as potentially leading to much smaller Auger scattering rates than found in III-V material systems. However, theory predicts that there may nevertheless still remain a substantial contribution to this unwanted recombination process through intervalley scattering, [1][2][3][4] although later theories, [2][3][4] including more realistic band-structure pictures, suggest that this should not be as serious as originally predicted. 1 Understanding accurately how the recombination processes change with carrier density is important for emission devices which operate far from equilibrium, and in particular in the continuing quest for the development of compact MIR room-temperature lasers.…”
Section: Introductionmentioning
confidence: 95%
“…The sophistication of a three-beam pump-probe experimental technique described below has enabled an analysis of the decay at times longer than 100 ps in terms of the nonparabolic anisotropic band structure of the lead salts, to give the Auger coefficient C qualitatively over a wide temperature range 30-300 K. The results are in good agreement with theory for nonparabolic, anisotropic bands 11,12 and nondegenerate statistics, 2 and confirm that the original parabolic band calculations 1 underestimated the measured lifetime by more than an order of magnitude. [2][3][4]6 Finally the Auger results for the lead salts are compared with earlier measurements taken at FELIX ͑Ref. 13͒ for Hg 1Ϫx Cd x Te of a composition such that the band gap for the two semiconductors is the same at Tϭ100 K. 13 It is found that C for PbSe is between one and two orders of magnitude lower than for Hg 1Ϫx Cd x Te over the whole temperature range for comparable values of the band gap.…”
Section: Introductionmentioning
confidence: 95%
“…A characteristic two-valley process [3] dominates the Auger recombination in lead chalcogenides with strong anisotropic band structure (e.g. PbTe, PbSnTe).…”
Section: The Activation Energymentioning
confidence: 99%
“…For bulk lead chalcogenides it is well-known [3] that increasing band stucture anisotropy and decreasing gap energy (following e.g. the series PbSSe, PbSnSe, PbSnTe) give rise to an increasing Auger recombination rate.…”
Section: Introductionmentioning
confidence: 99%